2023
DOI: 10.3390/genes14061268
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome-Level Genome Assembly Provides Insights into the Evolution of the Special Morphology and Behaviour of Lepturacanthus savala

Abstract: Savalani hairtail Lepturacanthus savala is a widely distributed fish along the Indo-Western Pacific coast, and contributes substantially to trichiurid fishery resources worldwide. In this study, the first chromosome-level genome assembly of L. savala was obtained by PacBio SMRT-Seq, Illumina HiSeq, and Hi-C technologies. The final assembled L. savala genome was 790.02 Mb with contig N50 and scaffold N50 values of 19.01 Mb and 32.77 Mb, respectively. The assembled sequences were anchored to 24 chromosomes by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 141 publications
2
6
0
Order By: Relevance
“…The size of the final assembled genome was 709.27 Mb, with a GC content of 40.81%, a heterozygosity rate of 1.18%, and a repetitive sequence rate of 35.43%. These values were generally close to the results of the E. muticus genome survey (670 Mb, 41.68%, 1.26%, 35.33%) reported by Song et al [70], but differed significantly from the results of the L. savala genome (790.02 Mb, 39.03%, 0.53%, 40.54%) as determined by Wu et al [23]. The rate of repetitive sequences is a key factor influencing the genome size of species [71].…”
Section: Characterization Of the E Muticus Genomesupporting
confidence: 86%
See 4 more Smart Citations
“…The size of the final assembled genome was 709.27 Mb, with a GC content of 40.81%, a heterozygosity rate of 1.18%, and a repetitive sequence rate of 35.43%. These values were generally close to the results of the E. muticus genome survey (670 Mb, 41.68%, 1.26%, 35.33%) reported by Song et al [70], but differed significantly from the results of the L. savala genome (790.02 Mb, 39.03%, 0.53%, 40.54%) as determined by Wu et al [23]. The rate of repetitive sequences is a key factor influencing the genome size of species [71].…”
Section: Characterization Of the E Muticus Genomesupporting
confidence: 86%
“…The number of chromosomes in the assembled genome of E. muticus was 24, consistent with that of L. savala, T. albacares, and T. maccoyii [23]. The ML tree results indicated that the phylogenetic relationships of these four species were consistent with their morphological classification [72].…”
Section: Characterization Of the E Muticus Genomesupporting
confidence: 58%
See 3 more Smart Citations